New Structural and Mechanistic Insights Into Functional Roles of Cytochrome b559 in Photosystem II - Chiu, Yi-Fang; Chu, Hsiu-An (Frontiers in Plant Science, 2022)
Cytochrome (Cyt) b559 is a key component of the photosystem II (PSII) complex for its assembly and proper function. Previous studies have suggested that Cytb559 has functional roles in early assembly of PSII and in secondary electron transfer pathways that protect PSII against photoinhibition. In addition, the Cytb559 in various PSII preparations exhibited multiple different redox potential forms. However, the precise functional roles of Cytb559 in PSII remain unclear. Recent site-directed mutagenesis studies combined with functional genomics and biochemical analysis, as well as high-resolution x-ray crystallography and cryo-electron microscopy studies on native, inactive, and assembly intermediates of PSII have provided important new structural and mechanistic insights into the functional roles of Cytb559. This mini-review gives an overview of new exciting results and their significance for understanding the structural and functional roles of Cytb559 in PSII.